KUALITAS PELAYANAN DAN KEPUASAN WAJIB PAJAK - Arisanti, Yessie (Jurnal Ilmu Administrasi Negara, 2016)
Service Quality and Satisfaction Taxpayer. This study aims to determine the effect of service quality to satisfaction of the taxpayer at the Regional Revenue Departement Bengkalis. This type of research is a survey research. The study population was taxpayers (both individual and corporate) are subject to tax payment obligation BPHTB. Total sample of 100 people conducted by accidental. Collection techniques by observation, questionnaire and documentation. Data analysis methods used is Multiple Linear Regression with SPSS version 17 for Windows. The results showed that the dimensions of service quality (reliability, responsiveness, assurance, empathy, physical form) simultaneously and partially positive and significant effect on taxpayer satisfaction. Variable empathy is the dominant variable influencing satisfaction of taxpayers.